Comparing the vocal techniques of jazz and classical music - Crabtree, Jacob (2024)
This research will highlight some of the main vocal and performance techniques found within the two fields of classical and jazz music. I will start with a brief history on the two genres of music, showing the social differences and journeys that the two had to take to get to the prominent position they both still hold today. I will then go on to explain the commonly used vocal techniques, various methods of teaching and performance practices that both jazz and classical music maintain before then showing how similar they are at base value. I also aim to show that some of the techniques used within both genres are interchangeable, exploring the idea that once the skills are solidified for one genre, a vocalist is already equipped with some of the basic skills to perform the other. Having been a chorister within a cathedral choir since a young age and a classically trained tenor for many years that has also been a member of popular and jazz music ensembles, this is a topic that has always interested me. Through my years of performing at both classical recitals and jazz gigs, I have always been aware that there have been physical changes in my singing technique to offer a convincing and true performance in both genres. However, I wanted to use this opportunity of research to highlight what exactly is done differently, whilst also analysing the similarities in these differing vocal styles.